2020
DOI: 10.29057/lc.v2i3.6144
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of objective formative assessment in language learning

Abstract: The objective of this report was to describe the significant role that the objective formative assessment plays in learning a language. To do this, the information and data were displayed to prove if the use of objective formative assessment is an appropriate way to increase language learning. Data was collected with a questionnaire that covered individuals' perception of exams, mid-term exams, short-practice-exams / quizzes, self-evaluations, and exercises with scores. The frequency statistical test was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The theory fits well with this study because it aimed at examining the extent to which the assessment techniques that mathematics teachers use in secondary schools assessed soft skills. This is because the sole purpose of assessment, among many others, is to diagnose student learning difficulties, provide feedback, help in planning how to carry out instruction, and maintain social balance in the learning process (Guevara-Bazán et al, 2020). Gibb (2014) summarizes that in control theory, the assessor (teacher) can diagnose the lack of capacity in the attainment of soft skills on the part of the recipient (student) and adjust instructions and provide feedback to close the gap.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory fits well with this study because it aimed at examining the extent to which the assessment techniques that mathematics teachers use in secondary schools assessed soft skills. This is because the sole purpose of assessment, among many others, is to diagnose student learning difficulties, provide feedback, help in planning how to carry out instruction, and maintain social balance in the learning process (Guevara-Bazán et al, 2020). Gibb (2014) summarizes that in control theory, the assessor (teacher) can diagnose the lack of capacity in the attainment of soft skills on the part of the recipient (student) and adjust instructions and provide feedback to close the gap.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Through assessment evidence of an individual, student's learning progress is collected, interpreted and later judgments are made about the students' accomplishments following some set standards (Guevara-Bazán et al, 2020). Guevara-Bazán et al (2020); the Ministry of Education [MINEDUC] and Rwanda Education Board [REB] (2015b) also concurred that the purpose of assessment is for monitoring students' progress, providing feedback on students' performance, guidance on future progressions, promotion, selection and certification. The Curriculum Development Centre [CDC] (2013e) and Tejeda and Gallardo (2017) stated that assessment must match the aims of the curriculum so that it supports teaching and learning.…”
Section: Introduction 11 Background To the Problemmentioning
confidence: 99%
“…The target to be achieved in this community service program is to increase teaching literacy for junior high school English teachers in remote and isolated areas in Toba Regency, North Sumatra. Observations made by the community service team revealed that teachers had not been able to determine the competencies that students had to achieve in each material, the application of teaching practices was still focused on activities originating from textbooks and learning evaluations were not well designed, in fact they only relied on the exercises contained in the textbook (Susan et al, 2020;Guevara-Bazán et al, 2020).…”
Section: Introduction General Descriptionmentioning
confidence: 99%